Unilateral moyamoya disease with co-existing arteriovenous malformation - Nawawi, Ouzreiah; Sinnasamy, Moorthy; Mohd Ramli, Norlisah (British Institute of Radiology, 2006)
A case of an intracerebral bleed in a young man with a rare combination of arteriovenous malformation (AVM) and unilateral moyamoya disease is presented. The location of the bleed in the left basal ganglia corresponded to the area supplied by the basal moyamoya vessels. The AVM which received supply from collateral moyamoya vessels as well as normal cerebral arteries was located in the ipsilateral parieto-occipital region posterior to the basal ganglia bleed. This is the first reported cerebral AVM co-existing with a unilateral moyamoya disease in the English literature. Unusual features of the case such as the unilaterality of the angiographic abnormalities, their coexistence and hypotheses as to their development are discussed.